Effects of aminoethoxyvinylglycine and modified atmosphere packaging treatments on the color characteristics and antioxidant activity of kiwifruit during cold storage and shelf life - Uzun, S; Ozturk, B (Journal of Postharvest Technology, 2020)
This study was carried out to determine the effects of postharvest aminoethoxyvinylglycine (AVG) and modified atmosphere packaging (MAP) treatments on color characteristics and antioxidant activity of kiwifruit (Actinidia deliciosa L.) fruit during cold storage and shelf life. Control, AVG, MAP, and AVG+MAP treatments were designed in the study. During the study, L *, chroma, and hue angles were determined in terms of color characteristics of fruits. Also, the FRAP assay was applied to determine antioxidant activity. L* values (on 60th, 90th, and 120th days) and chroma values (on 120th and 150th days) were higher than the control in cold storage. In shelf life, L* values (90th and 180th days) and chroma values (on 90th, 120th, and 150th days) in all treatments were higher than the control. During cold storage (except for 30th day), higher hue angle values were obtained from fruit treated with MAP. In the last two measurements period of shelf life, the lowest hue angle values were determined in control fruit. At the end of cold storage, the highest antioxidant activity was obtained in AVG treatment. During shelf life, antioxidant activity was higher in AVG and MAP treatments than the control. In the study, it was revealed that the MAP treatment was especially effective in color development, but more effective results were obtained from the combination of MAP and AVG. Also, it was revealed that the AVG and MAP treatments could be used to maintain antioxidant activity.